ESKAPE pathogens: antimicrobial resistance, epidemiology, clinical impact and therapeutics - Miller, William R; Arias, Cesar A (Nature reviews. Microbiology, 2024)
The rise of antibiotic resistance and a dwindling antimicrobial pipeline have been recognized as emerging threats to public health. The ESKAPE pathogens - Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp. - were initially identified as critical multidrug-resistant bacteria for which effective therapies were rapidly needed. Now, entering the third decade of the twenty-first century, and despite the introduction of several new antibiotics and antibiotic adjuvants, such as novel β-lactamase inhibitors, these organisms continue to represent major therapeutic challenges. These bacteria share several key biological features, including adaptations for survival in the modern health-care setting, diverse methods for acquiring resistance determinants and the dissemination of successful high-risk clones around the world. With the advent of next-generation sequencing, novel tools to track and combat the spread of these organisms have rapidly evolved, as well as renewed interest in non-traditional antibiotic approaches. In this Review, we explore the current epidemiology and clinical impact of this important group of bacterial pathogens and discuss relevant mechanisms of resistance to recently introduced antibiotics that affect their use in clinical settings. Furthermore, we discuss emerging therapeutic strategies needed for effective patient care in the era of widespread antimicrobial resistance.